2012
DOI: 10.1039/c2ob25683e
|View full text |Cite
|
Sign up to set email alerts
|

Structural diversity in native cyclodextrins/folic acid complexes – from [2]-rotaxane to exclusion compound

Abstract: The formation of different complexes of folic acid depending on the size of the host cyclodextrin resulting in either an exclusion compound (with the smallest α-cyclodextrin) or 2-rotaxane, where cyclodextrin is threaded over folic acid (with β- and γ-cyclodextrins), is presented. The formation is carried out in water which allows both possible application in pharmaceutical sciences and usage of environmentally friendly "green chemistry". The obtained compounds are thoroughly characterized using one and two di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 12 publications
2
23
0
Order By: Relevance
“…Moreover, T 1 values of the 6CN10 hydrogens signals change between the free and the complexed states, indicating a change of 6CN10 dynamics, which suggest the existence of formation of both complexes (1:2 and 1:1 molar ratios) ( Table 1). 35,36 To obtain further information on the complex formation, 2D ROESY experiments were performed in order to evaluate the mode of complexation and spatial arrangement between 6CN10 and HP-β-CD atoms. Intermolecular cross-peaks were observed between imine and aromatic hydrogens of 6CN10 and HP-β-CD hydrogens (Figure 5), corroborating the 1 H NMR data that showed that the major changes in the chemical shifts happened in the imine and aromatic hydrogens of 6CN10 in complex.…”
Section: D and 2dmentioning
confidence: 99%
“…Moreover, T 1 values of the 6CN10 hydrogens signals change between the free and the complexed states, indicating a change of 6CN10 dynamics, which suggest the existence of formation of both complexes (1:2 and 1:1 molar ratios) ( Table 1). 35,36 To obtain further information on the complex formation, 2D ROESY experiments were performed in order to evaluate the mode of complexation and spatial arrangement between 6CN10 and HP-β-CD atoms. Intermolecular cross-peaks were observed between imine and aromatic hydrogens of 6CN10 and HP-β-CD hydrogens (Figure 5), corroborating the 1 H NMR data that showed that the major changes in the chemical shifts happened in the imine and aromatic hydrogens of 6CN10 in complex.…”
Section: D and 2dmentioning
confidence: 99%
“…[48,49] In general, the electrostatic forces are strengthened in vacuum, whereas the hydrophobic interactions become weaker.T his means that the most stable complexes in MS experiments are those in which the hydrogen-bonding and electrostatic interactions play ac rucial role in the formation of noncovalent systems. This method allows the strengtho fi nteractions of molecules in noncovalent complexes to be determined.…”
Section: Ms Studies On Gas Phase Complexation Of Aggregates Of Isotrimentioning
confidence: 99%
“…A large number of studies have been devoted to investigating the relative stability of noncovalent complexesi nt he gas phase. [48,49] In general, the electrostatic forces are strengthened in vacuum, whereas the hydrophobic interactions become weaker.T his means that the most stable complexes in MS experiments are those in which the hydrogen-bonding and electrostatic interactions play ac rucial role in the formation of noncovalent systems. However,o ther factors such as the entropic factor and the kinetic versus thermodynamic stability also should be considered when comparing gas phase and solution stability measurements of noncovalent complexes.…”
Section: Ms Studies On Gas Phase Complexation Of Aggregates Of Isotrimentioning
confidence: 99%
“…The key points for the possible application of the FA‐targeted materials are (i) the level of the cellular uptake of FA and (ii) their cytotoxicity toward cancer cells. What is more important, there are articles reporting the inclusion of FA via the aromatic part of its structure into the interior of βCD . However, the possible limiting of the biological activity of FA in the covalent nanotherapeutic systems consisting of βCD has not been discussed in the literature up to date.…”
Section: Introductionmentioning
confidence: 99%
“…What is more important, there are articles reporting the inclusion of FA via the aromatic part of its structure into the interior of βCD. [26,27] However, the possible limiting of the biological activity of FA in the covalent nanotherapeutic systems consisting of βCD has not been…”
mentioning
confidence: 99%